The consistency of vitamin B12 in marketed microalgae powders - Md Mirazul Islam, (International Journal of Agricultural Research, Innovation and Technology, 2025)
Vitamin B12 is a water nutrient that plays a key role, in DNA replication and the production of red blood cells as well as maintaining proper neuron function in the body system. Insufficient levels of this vitamin can result in health complications like megaloblastic anemia. At times, microalgal powders have surfaced as a source of vitamin B12. The purpose of this study is to investigate the amount of active vitamin B12 in microalgae with a specific focus on commercially available strains, like Chlorella sp. and Nannochloropsis gaditana. The research discovered that Chlorella sp. and N. gaditana powders have vitamin B12 levels of, up to 2.1 µ/g whereas Spirulina powders contain pseudo vitamin B12 than active B12. Collectively speaking Chlorella sp. and N. gaditana serve as good sources of active vitamin B12 while Spirulina seems to be less potent due, to its high pseudo-vitamin B12 content. This research highlights the promise of powders, like Chlorella sp. and N. gaditana as sources of accessible vitamin B12 that may contribute to addressing nutritional gaps in diets. Int. J. Agril. Res. Innov. Tech. 14(2): 146-152, December 2024